2021
DOI: 10.2217/imt-2020-0311
|View full text |Cite
|
Sign up to set email alerts
|

Atezolizumab with bevacizumab, paclitaxel and carboplatin was effective for patients with SMARCA4-deficient thoracic sarcoma

Abstract: SMARCA4-deficient thoracic sarcoma (DTS) is a recently noted progressive thoracic malignancy. We recently experienced three cases of SMARCA4-DTS who were treated with atezolizumab in combination with bevacizumab, paclitaxel and carboplatin (ABCP) as the first-line therapy. Immunohistopathological analysis revealed absent expression of SMARCA4 in all cases. The tumor mutational burden was over 11/Mb and mutations in SMARCA4 and TP53 were detected in all three cases. Partial response to ABCP treatment was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…In this study, we found that SMARCA4-related genes were enriched in the PPAR signaling pathway and identified a strong correlation among SMARCA4, CD274, and PDCD1. Furthermore, the expression levels of SMARCA4 were found to be positively correlated with immunotherapy, which were consistent with the study reported by Peng et al [ 22 ], and was further confirmed in the patients with thoracic sarcoma and pancreatic cancer[ 19 , 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found that SMARCA4-related genes were enriched in the PPAR signaling pathway and identified a strong correlation among SMARCA4, CD274, and PDCD1. Furthermore, the expression levels of SMARCA4 were found to be positively correlated with immunotherapy, which were consistent with the study reported by Peng et al [ 22 ], and was further confirmed in the patients with thoracic sarcoma and pancreatic cancer[ 19 , 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…7,8 Although the efficacy of anti-angiogenic agents in sarcoma has not been established, it has been reported that treatment with atezolizumab, bevacizumab, carboplatin, and paclitaxel was effective in thoracic SMARCA4-deficient undifferentiated tumors. 9 Our patient was treated with atezolizumab, carboplatin, and nab-paclitaxel, excluding anti-angiogenic agents for hemoptysis, and achieved stable disease for 7 months.…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that the therapeutic effect was obtained using the anti‐PD‐L1 antibody in thoracic SMARCA4‐deficient undifferentiated tumors, regardless of the degree of PD‐L1 expression 7,8 . Although the efficacy of anti‐angiogenic agents in sarcoma has not been established, it has been reported that treatment with atezolizumab, bevacizumab, carboplatin, and paclitaxel was effective in thoracic SMARCA4‐deficient undifferentiated tumors 9 . Our patient was treated with atezolizumab, carboplatin, and nab‐paclitaxel, excluding anti‐angiogenic agents for hemoptysis, and achieved stable disease for 7 months.…”
Section: Discussionmentioning
confidence: 99%
“…SMARCA4‐UT is generally insensitive to cytotoxic chemotherapy; therefore, in this case, we did not administer adjuvant chemotherapy. Although three recent cases of unresectable SMARCA4‐UTs receiving combined immunotherapy, including atezolizumab, showed a strong effect (up to 17 months progression‐free survival), 5 there are no reports on the efficacy of immune checkpoint inhibitors (ICI) as adjuvant chemotherapy. Owing to the aggressive growth of these tumours, once symptoms appear, continuing treatment is frequently difficult, with decreased patient performance status.…”
Section: Discussionmentioning
confidence: 99%